Emerging dynamic structure of electrocatalysts unveiled by in situ X-ray diffraction/absorption spectroscopy. Issue 4 (10th March 2021) - Zhu, Yanping; Kuo, Tsung-Rong; Li, Yue-Hua; Qi, Ming-Yu; Chen, Gao; Wang, Jiali; Xu, Yi-Jun; Chen, Hao Ming
Abstract : This review proposed dynamic structural reconstruction/transformation routes for OER and CO2 RR electrocatalysts based on in situ X-ray diffraction/absorption spectroscopy. Abstract : Highly-efficient oxygen evolution reaction (OER) and reduction of carbon dioxide (CO2 RR) represent the two biggest scientific challenges in artificial photosynthesis. Many efficient and cost-affordable electrocatalysts have been reported in the development of electrochemical OER and CO2 RR; however, during the electro-derived oxidation or reduction processes, a critical fact that, most catalysts tend to undergo structural reconstruction and/or surface rearrangement, has been widely observed, which greatly subverts the traditional conception of "catalysts". In this respect, the research trends have gradually transferred from optimizing catalyst materials to elucidating the real active sites of the catalysts as well as understanding the underlying mechanisms behind these complex reactions. Most importantly, the in situ / operando characterization techniques are powerful tools to achieve this goal. Herein, recent advances in the in situ X-ray diffraction and absorption spectroscopy that have provided a unique opportunity to investigate the structural reconstruction and/or surface rearrangement of catalysts under realistic OER and CO2 RR conditions are thoroughly reviewed. Finally, the challenges of the material design are discussed, and the future perspective for developing next-generation catalysts with imperative requirements of material nature is provided.